Influence of Cutting Tool Wear when Milling Inconel 718 on Resulting Roughness - Mrkvica, Ivan; Špalek, František; Szotkowski, Tomáš (Manufacturing Technology Journal, 2018)
At present, a large spectrum of cutting tools and machines is available. Therefore, cutting of difficult to cut materials seems not to be a problem which could not be solved by an appropriate choice of cutting system. This article deals with wear of cutting tool edges when milling a superalloy Inconel 718 and its direct influence on resulting roughness of a machined surface. Combinations of different cutting speeds and feeds have been performed. A criterion of flank wear amounting to VB=0.7 mm was chosen for machined material Inconel 718 and used cutting materials in combination with cutting conditions. Regarding the exacting character of the test it was necessary to use an as solid as possible machine, that is why a 3-axis CNC milling machine was chosen. All tests were performed with process liquid because of extremely high temperatures which occur.
Keywords: milling; Inconel 718; cutting speed; roughness